2011
DOI: 10.1111/j.1365-2486.2011.02515.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting phenology by integrating ecology, evolution and climate science

Abstract: Forecasting how species and ecosystems will respond to climate change has been a major aim of ecology in recent years. Much of this research has focused on phenology -the timing of life-history events. Phenology has well-demonstrated links to climate, from genetic to landscape scales; yet our ability to explain and predict variation in phenology across species, habitats and time remains poor. Here, we outline how merging approaches from ecology, climate science and evolutionary biology can advance research on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
366
5
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(394 citation statements)
references
References 83 publications
13
366
5
4
Order By: Relevance
“…The lack of responsiveness to August climate is unlikely to be due to the result of changes in growing season length, because in almost all years there was still production and green leaf area throughout August. One distal explanation of why favorable August climates are not associated with greater productivity could be phenological (40). Similar to long-lived temperate trees senescing in conjunction with photoperiod cues to minimize damage from low temperatures (41), there might be an evolutionary response of the predominant long-lived C 4 grasses (42) to minimize the risks associated with the extreme environmental conditions observed in August by adjusting their timing of reproduction and senescence (17,43).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of responsiveness to August climate is unlikely to be due to the result of changes in growing season length, because in almost all years there was still production and green leaf area throughout August. One distal explanation of why favorable August climates are not associated with greater productivity could be phenological (40). Similar to long-lived temperate trees senescing in conjunction with photoperiod cues to minimize damage from low temperatures (41), there might be an evolutionary response of the predominant long-lived C 4 grasses (42) to minimize the risks associated with the extreme environmental conditions observed in August by adjusting their timing of reproduction and senescence (17,43).…”
Section: Resultsmentioning
confidence: 99%
“…Variation in flowering time relative to vegetative phenology, induced by a variety of factors (significant rain in winter/summer, decreasing or increasing photoperiod, or drought-induced leaf-fall), results in a number of flowering patterns in tropical trees (Borchert et al 2004). Phenological processes are significant constituents of plant fitness, since the time and duration of vegetative and reproductive cycles affect the capability of a plant species to establish itself in a given site (Pau et al 2011). Singh & Kushwaha (2005) suggested that climate change forced deviations in the length of the growing period, and competition among species may change the resource use patterns in different species.…”
Section: Introductionmentioning
confidence: 99%
“…Phenology, the science of natural recurring events (Demarée and Rutishauser, 2011) analyses the timing of periodic life-history events (i.e. phenophases) such as budburst or first flowering of plants (Pau et al, 2011). Specifically, the first definition by Lieth (1974) says: 'Phenology is the study of timing of recurrent biological events, the causes of their timing with regard to biotic and abiotic forces, and the interrelation among phases of the same or different species'.…”
Section: Introductionmentioning
confidence: 99%